2021
DOI: 10.1111/opn.12427
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' experiences of using a biopsychosocial approach to understand behavioural and psychological symptoms of dementia: A qualitative interview study

Abstract: Background: Biopsychosocial approaches to understanding behavioural and psychological (otherwise known as "non-cognitive" or "neuropsychiatric") symptoms of dementia tend to be conducted by specialist psychology professionals. To increase service users' access to these approaches, healthcare professionals from nursing and allied health disciplines are being trained to use them. However, little is known about healthcare professionals' experiences of implementing biopsychosocial approaches in everyday practice.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Working together formed another pertinent theme within the present study and was also identified within Steele et al’s (2021) study exploring community mental health staff members’ experiences of carrying out formulations with care home staff. Participants within the present study discussed feeling that the psychologist had not attained a true perspective of the resident in question as the care staff had not been suitably involved in the information gathering process.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Working together formed another pertinent theme within the present study and was also identified within Steele et al’s (2021) study exploring community mental health staff members’ experiences of carrying out formulations with care home staff. Participants within the present study discussed feeling that the psychologist had not attained a true perspective of the resident in question as the care staff had not been suitably involved in the information gathering process.…”
Section: Discussionmentioning
confidence: 74%
“…If staff do not understand the purpose or the nature of the formulation developed, they are unlikely to appreciate the value of recommendations arising within from the process. Previous research has suggested that one of the key barriers to carrying out effective formulation is information generated from formulations not being fed into care planning (Steele et al, 2021). These findings suggest that managing staff expectations and engaging staff in a way that recognises the perspectives that they themselves bring is a way of overcoming this barrier, supported by psychological theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least one-quarter of people in Sub-Saharan Africa have experienced a psychotic disorders at some point in their lives (Galvin & Byansi, 2020;Roberts, Smith, Cluver, Toska, & Sherr, 2021). The WHO"s slogan of 2004, which stated that "no health without mental health," wants mental health to be viewed in biological, psychological, and sociological domains through a model known as the biopsychosocial approach (Vigo, et al, 2016;Ng et al, 2021;Peña-Vargas, Armaiz-Peña, & Castro-Figueroa, 2021;Steele, Berry, & Brown, 2022). The slogan also insists on the involvement of the entire community in the improvement of the mental wellbeing of those suffering from mental illnesses.…”
Section: Introductionmentioning
confidence: 99%